التشبيه في القرآن: دراسۃ التفسیر للراغب الأصفهانيMetaphor in the Quran: A Study of Qur’ānic Exegesis by Rāghib al-Isfahānī (Al-Qamar, 2021)
This paper studies the use of Metaphor in the Quran in light of the commentary of the Quran by Rāghib al-Isfahānī (d. 502 AH), a renowned expert of Qur’ānic exegesis and writer of the most celebrated dictionary of Qur’ānic terms titled “al-Mufradāt fī Gharīb al-Quran”. A metaphor is a figure of speech that is used to make a comparison between two things that aren’t alike but do have something in common unlike a simile, where two things are compared directly using like or as a metaphor’s comparison is more indirect, usually made by stating something is something else. This study mentions various analogies from the Qur’ānic exegesis by al-Isfahānī.
Keywords: Metaphor; Quran; Tafsīr; Rāghib al-Isfahānī